Why can’t I get a job? exploring the drivers of perceived employability among fine art graduates - Wang, Jing; Lim, Xin-Jean; Ng, Siew Imm (Springer, 2023)
As a newly rising economic power, China is considered to have a huge job market. However, many graduates in China experience substantial pressure in getting a job upon graduation, as a university degree is no longer a “golden ticket” to employment. In this study, we aim to understand the underlying factors that influences fine arts graduates’ perceived employability, by incorporating the human capital theory and self-determination theory. Using an online survey, data was collected from 430 final year fine arts students from Guangxi, China. The findings showed that self-directed learning and career adaptability positively impacts perceived employability. While these relationships are found stronger when if graduates continue to receive advice and assistance from their lecturers. Altogether, these outcomes offer several implications that useful for academics and practitioners to manage employability issues more effectively.